Terapi Rabbani Dalam Merawat Masalah Neurosis: Rabbānī Therapy in Treating Neurosis Problem - Kamarul Zaman, Rahim; Che Nordin, Mohd Khairul Naim; Nasir, Khairulnazrin (Afkar: Jurnal Akidah dan Pemikiran Islam, 2021)
Al-Qur’ān has described anxiety as part of human nature. Anxiety in the context of psychology is categorized as a mental disorder problem in the category of neurosis. Neurotic problems can occur when someone faces disruptions in terms of internal interaction or social environment. Its effects can have adverse implications on behavior and thinking resulting in suffering to patients. However, al-Qur’ān also contains some verses that can be applied as a therapy to treat human anxiety. Based on the content analysis approach to the text of Quranic verses, this paper presents a reflection on various forms of rabbānī therapy to address the problem of neurosis. The findings of the study demonstrate that al-Qur’an is a treasure of alternative treatment mechanisms that is applicable to patients with mental disorders of the neurosis category. In conclusion, Islam is proven to have pioneered a variety of solutions to life problems, especially those related to mental disorders.